College degree attainment by age of first marijuana use and parental education. Issue 1 (2nd January 2019) - Linden-Carmichael, Ashley N.; Kloska, Deborah D.; Evans-Polce, Rebecca; Lanza, Stephanie T.; Patrick, Megan E.
Abstract: Background: Age of first marijuana use is a key predictor of later educational outcomes, but limited work has identified demographic factors that impact this association across continuous ages of first use. The purpose of this study was threefold: (1) to identify the age-varying prevalence of later college degree attainment as a function of age of first marijuana use; (2) to examine the age-varying association of gender and college degree attainment as a function of age of first use; and (3) to examine the age-varying association of parent education and college degree attainment as a function of age of first use. Methods: Data were from the panel portion of the Monitoring the Future (MTF) study, an ongoing longitudinal study of adolescents and young adults. Those who used marijuana by age 22 were included in analyses. Among these participants ( N  = 2134), 47.0% were male, 67.5% were white, 53.2% reported having at least one parent with a bachelor's degree or higher, and 44.1% attained a bachelor's degree or higher by age 25/26. Results: Intercept-only and logistic time-varying effect models (TVEMs) modeled prevalences and associations as functions of age of first marijuana use. Prevalence of college degree completion was relatively linear across age of first use; such that college degree attainment increased as age of first use increased. Results indicated that college degree attainment varied across age of first use similarly for men and women. Degree attainment differences existed based on parent education. Parental education and degree attainment were most strongly linked at an age of first use between 16 and 19 years. Conclusions: Findings suggest that age of first marijuana use has an association with academic achievement such that earlier ages of first use are associated with lower academic achievement later in adulthood. Parental education serves as a protective factor against college degree attainment in late adolescence.